PERBANDINGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK PESERTA DIDIK YANG PEMBELAJARANNYA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL DISCOVERY LEARNING (DL) - Galuh Oktagina; Evan Farhan Wahyu Puadi; Uba Umbara (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
The purpose of this research is to know which ability of creative thinking of mathematic learners better between using Problem Based Learning (PBL) model and Discovery Learning (DL) model. The research method used is experimental research method. Based on the results of research and data analysis, researchers then use the Mann-Whitney Test (U) to examine differences in learning outcomes. From the calculation results obtained value of U = 427,5. Since there are several twin numbers then correction of standard deviation is then used to find the value of z. The value of U is first converted to z value because the research zhitung = 2,93 while ztabel at a significant level of 0,05 is 1,96. When consulted in table z, the z-value is outside the reception area H0. This is because the test used is a one-party test with acceptance criteria is accept H0 if and reject H0 in other situations. As we know that the value of zhitung > z0,475 then accept H1, that is there are differences in the ability of creative thinking mathematic learners using Problem Based Learning model using Discovery Learning model.Student's response to Problem Based Learning model is quite good. If we accumulate 52,6% student answer show response strongly agree and agree that we can translate as positive response, 19,78% neutral response and the rest only 27,61% student disagree and strongly disagree what we mean as negative response.